Comparative analysis of conventional and new seismically isolated structure - Ristić Jelena (Society for Materials and Structures testing of Serbia, 2021)
Extensive analytical and experimental research has been done by the authors directed to mitigation of the effects of earthquakes on structures. The research results mainly represent parts of the realized several related international projects. A selected part of the analytical studies directed to comparison between conventional and seismically isolated frame structures is presented in this paper. The responses of the applied newely developed advanced seismic isolation system HC-RMS-GOSEB to the simulated input excitation of three representative earthquakes of intensity 0.50g, have shown that it is very effective for construction of vibro-isolated and seismically resistant buildings, providing activated multistage seismic response and globally optimized seismic energy balance. Its application achieves an increase in the vibration period of the structure, far enough from the dominant period of seismic excitation. The results of the research confirm that this system is a potential solution for achieving low-cost and highly efficient protection of buildings.